Penggunaan Silica Fume Sebagai Substitusi Semen Dengan Bahan Tambah Abu Pecahan Karang Pada Beton - Andika Pasulu; Jonie Tanijaya; Desi Sandy (Paulus Civil Engineering Journal, 2023)
Silica Fume is a very fine pozzolan material, which contains more silica composition than the rest of silicon production or silicon iron alloys. Silica fume is used in the form of powder as a cement substitution. This study aims to determine the effect of percentages using silica fume as a substitution of cement with coral fragment ash added material on the compressive strength, tensile strength and modulus of elasticity of concrete. This research is the SNI (f'c) 30 MPa method and a sample of cylindrical formations with dimensions of 150 mm x 300 mm. Based on the results of the study obtained, variations of Silica fume 9% and Coral Fractional Ash 0%, 5%, 7.5%, 10% obtained compressive strength values aged 28 consecutive days were 30,951 MPa, 32,744 MPa, 31,989 MPa, and 31,423 MPa, sample tensile strength test results of 3,161 MPa, 3,397 MPa, 3,491 MPa, and 3,303 MPa, elasticity modulus results of 28233,7885 MPa, 33486,8743 MPa, 32409.6667 MPa, and 30350.5834 MPa. From the results of research, the use of silica fume and coral fragment ash in concrete can affect the strength of concrete, where the value obtained varies. Compressive strength and elasticity modulus are maximum at 5% variation and maximum split tensile strength at 7.5% variation.